Kétnyelvűség és nyelvhasználat a muravidéki magyarok körében - Szabó, Ildikó (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 1993)
The first part of the article provides data on the introduction of bilingual school in Prekmurje, giving a brief outline of demographic characteristics of Hungarians in Prekmurje, legal guarantees and research methods. The second part deals with the use of mother tongue in different situations, whereby the authoress ascertains that Hungarian language is subject to discriminatory treatment in public life. The research focuses on the study of the role of kindergarten, i.e. the institution of socialization, which means the first encounter with official bilingualism for the youngest generation.
Keywords: dvojezičnost; jezikovne manjšine; Madžari; madžarščina; narodne manjšine; Prekmurje